Integrating Global Citizenship Education (GCED) Into Higher Education Islamic Curriculum as an Effort to Reconstruct Global Muslim Identity - Mufid, Muhammad; Muhlisin, Muhlisin; Jaeni, Muhammad; Huda, Miftahul (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2026)
This study aims to explore the reconstruction of a global Muslim identity by integrating Global Citizenship Education (GCED) values into the Islamic Religious Education curriculum. This study employed a qualitative case study approach at Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan. Data were gathered through participant observation, in-depth interviews, and documentation. Data analysis followed the interactive model of Miles, Huberman, and Saldaña, involving data condensation, data display, and conclusion drawing using multi-level thematic coding techniques to abstract raw field data into a new typology of piety. Data validity was ensured through source, technical, and theoretical triangulation. The findings indicate that the integration of GCED is implemented through three main pillars: interfaith dialogue, ecological ethics, and universal social justice. The reconstruction of identity is achieved by synergizing the doctrine of Rahmatan lil 'Alamin (a mercy to all creation) with the principles of global human rights. This integration engenders a typology of Cosmopolitan Sufism, a form of individual ritual piety that goes hand in hand with an active concern for the fate of humanity on a global scale. As a preliminary proposition, this study offers a "glocal" (global-local) Islamic Religious Education curriculum model that strengthens religious moderation at the higher education level. Practically, institutions need to incrementally revise Islamic Religious Education course syllabi and textbooks by incorporating case studies of global crises and peace solutions based on wasathiyah Islamic values.